2006
DOI: 10.1002/cne.20845
|View full text |Cite
|
Sign up to set email alerts
|

Localization of the urotensin II receptor in the rat central nervous system

Abstract: The vasoactive peptide urotensin II (UII) is primarily expressed in motoneurons of the brainstem and spinal cord. Intracerebroventricular injection of UII provokes various behavioral, cardiovascular, motor, and endocrine responses in the rat, but the distribution of the UII receptor in the central nervous system (CNS) has not yet been determined. In the present study, we have investigated the localization of UII receptor (GPR14) mRNA and UII binding sites in the rat CNS. RT-PCR analysis revealed that the highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
69
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 65 publications
(71 citation statements)
references
References 46 publications
1
69
0
1
Order By: Relevance
“…Central administration of UII has yielded more constant results, because in most species examined it evokes an increase in mean arterial pressure and heart rate through the activation of the peripheral sympathetic nervous system (Watson & May 2004, Le Mevel et al 2008. UTS2R1 mRNA can be detected in brainstem nuclei controlling cardiovascular homeostasis and in hypothalamic nuclei such as the paraventricular nucleus, which supports its role as a modulator of cardiovascular function (Jegou et al 2006). The URP mRNA is highly expressed in neurons that are intermingled with tyrosine hydroxylase-immunoreactive A1/C1 cells in the rostral ventrolateral medulla, indicating that URP may directly control adrenal sympathetic outflow.…”
Section: Uts2r5mentioning
confidence: 69%
See 2 more Smart Citations
“…Central administration of UII has yielded more constant results, because in most species examined it evokes an increase in mean arterial pressure and heart rate through the activation of the peripheral sympathetic nervous system (Watson & May 2004, Le Mevel et al 2008. UTS2R1 mRNA can be detected in brainstem nuclei controlling cardiovascular homeostasis and in hypothalamic nuclei such as the paraventricular nucleus, which supports its role as a modulator of cardiovascular function (Jegou et al 2006). The URP mRNA is highly expressed in neurons that are intermingled with tyrosine hydroxylase-immunoreactive A1/C1 cells in the rostral ventrolateral medulla, indicating that URP may directly control adrenal sympathetic outflow.…”
Section: Uts2r5mentioning
confidence: 69%
“…A number of behavioral effects of UII have been reported (Do Rego et al 2008), in line with the broad distribution of UTS2R1 mRNA and radiolabeled UIIbinding sites in the CNS (Jegou et al 2006). It is well established that UII is involved in various mood and sleep processes.…”
Section: Uts2r5mentioning
confidence: 79%
See 1 more Smart Citation
“…Vasoconstriction is not its only effect because UT receptors have been found in other organs. 43,44 Urotensin-II has also been shown to function as a potent vasodilator in some isolated vessels. 45 Norepinephrine: VSMC are primarily innervated by the sympathetic nervous system through adrenergic receptors.…”
Section: Urotensin-iimentioning
confidence: 99%
“…In addition, this peptide may contribute to the physiological regulation of cardiovascular homeostasis in humans (21,22). It was suggested that urotensin II can be used as a marker of myocardial and ischemia reperfusion injuries (23,24).…”
mentioning
confidence: 99%